Transillumination‐Guided Endoscopic Endonasal Dacryocystorhinostomy: Approach to Revision Cases and Challenging Anatomy. (23rd August 2013) - Vazquez, Alejandro; Blake, Danielle M.; Langer, Paul; Eloy, Jean A.
Abstract : Objectives: Dacryocystorhinostomy (DCR) is a surgical procedure whereby a connection is established between the lacrimal sac and the nasal cavity in an effort to bypass an obstruction of the distal lacrimal apparatus. Endoscopic endonasal DCR (EEDCR) is a minimally invasive technique used to achieve this goal. In patients with altered anatomy, EEDCR can be challenging. Here, we describe the use of canalicular transillumination with EEDCR in two complicated cases and discuss the benefits of this technique compared to external DCR and standard EEDCR. Methods: Case series. Results: A 33‐year‐old woman suffered an iatrogenic skull base injury while undergoing right‐sided EEDCR. An intraoperative rhinologic consultation was requested from our service, and the patient underwent emergent endoscopic repair of a right skull base defect. Grossly abnormal endoscopic and radiographic anatomy was noted, and a diagnosis of ozena was ultimately established. Two years later, the patient underwent successful right‐sided transillumination‐guided EEDCR (TG‐EEDCR). A 71‐year‐old woman who had previously undergone a right‐sided open DCR developed recurrent epiphora. Attempts to recanalize the fistula under endoscopic visualization was challenging due to the abnormal anatomy and excessive scarring. TG‐EEDCR was performed successfully. In both of these described cases, a 20‐gauge vitreoretinal light pipe was used for canalicular transillumination. Conclusion: EEDCR with canalicular transillumination represents a feasible alternative approach for cases in which prior surgery, trauma or other sinonasal pathology have significantly altered the native sinonasal/lacrimal anatomy.